Pelatihan dasar perancangan teknologi tepat guna berbasis mikrokontroler Arduino pada siswa SMAN 1 Parepare - Muh. Saleh; Jasruddin D. M; Nasrul Ihsan (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Extracurricular activities aim to enable students to develop their personality, talents, and abilities in various fieldsoutside the academic field, one of which is the field of appropriate technology. Based on the data obtained, there are 5 State HighSchools and 3 State Vocational Schools in Parepare City, Sulawesi Selatan and from the results of observations note that onlyone of these schools still facilitates students interested in the field of electronic-based appropriate technology. SMAN 1 Parepareis one of the model schools that cannot carry out this activity due to the unavailability of supporting resources in the field. Thesolution provided through the Community Partnership Program (PKM) activities is basic training in the design ofmicrocontroller-based appropriate technology. The method of implementing this PKM activity is a training method which isdivided into three stages, namely theoretical training, training on the use of Arduino IDE platform software and training ondesigning appropriate technology based on Arduino microcontrollers. The result of this PKM activity was to increase themotivation of SMAN 1 Parepare students in terms of students' interests, talents, and abilities in the form of simple, appropriatetechnology designs such as miniature automatic sensor-based control systems and Arduino microcontrollers.